PEMBINAAN KARAKTER SISWA MELALUI INTERNALISASI NILAI DALAM MOTTO PONDOK PESANTREN MODERN - Ajat Syarif Hidayatulloh; Asep Saepulmillah; Muhamad Tisna Nugraha; Aan Hasanah (Universitas Pahlawan Tuanku Tambusai, 2022)
The current of education tends is to emphasize improving cognitive abilities aspects of students' their affective and psychomotor aspects. In addition, the activities carried out focus more on the outward aspect than the inner one, so it is feared that it can give birth to people who lack empathy and pay attention to social elements. Whereas educational activities should ideally be able to combine the two elements that exist in students, namely the heart and mind, as well as outwardly and inwardly. Therefore, character education is the core of the education of the Indonesian nation in order to form intelligent, skilled, faithful, pious, and noble human beings. Character building can be carried out through various strategies and approaches, one of which is through the internalization of values ​​contained in the motto of Islamic boarding school education. The results of the study show that the development of Islamic character in SMP IT Al-Fawwaz students can be done through internalizing the values ​​contained in the motto of the modern Islamic boarding school Daarul Huda Balokang Banjar, including: virtuous, healthy, knowledgeable and free-thinking. These activities are carried out routinely in intra-curricular, co-curricular and extra-curricular activities which are guided directly by the teacher when the students are in school hours, as well as the ustadz when the students are in the dormitory. The results of this internalization are not only the formation of Islamic character of students, but also an increase in their learning achievement at school. Keywords: Development, Character, Internalization of Values.